A Lax Formalism for the Elliptic Difference Painlevé Equation - Yamada, Y. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
A Lax formalism for the elliptic Painlevé equation is presented. The construction is based on the geometry of the curves on P¹ × P¹ and described in terms of the point configurations.